Current Lung Asbestosis Approach for Diagnosis, Not Just Histopathology: A Literature Review - Purnama, Nori; Esha, Indi; Adrianison, Adrianison; Simanjuntak, Arya Marganda (Jurnal Respirologi Indonesia, 2025)
Asbestosis is characterized by diffuse interstitial fibrosis in the lungs, which is caused by breathing asbestos fibers from the crystalline or amphibole groups. The diagnosis of asbestosis, a form of pneumoconiosis, is one of the seven steps in identifying an occupational lung disease. Because there is no known cure for this condition, early detection, prevention, and education of workers and anybody in their proximity who has a risk of asbestos fiber exposure is critical. Clinical symptoms of asbestosis include weight loss, decreased appetite, and dyspnea during exertion. Clubbing fingers, cyanosis, and tachypnea are all symptoms of severe asbestosis. Bronchoalveolar lavage (BAL), histology, CT scans, HRCT, and respirometry can all help with the diagnosis. The "shaggy heart border sign" on a chest X-ray, along with the asbestos body observed in the BAL, is a reliable indicator of asbestosis. Because of the dismal prognosis and lifelong consequences, prevention is essential.